Rapidly evolving therapeutic advances for classical EGFR-mutant NSCLC - Pan, Kelsey; Ramalingam, Suresh S. (Frontiers in Oncology, 2025)
Epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC) has exemplified the advancement of precision oncology, yet inevitable resistance to tyrosine kinase inhibitors (TKIs) remains a challenge. Over the past decade, EGFR targeted therapies have extended beyond metastatic disease into early-stage and locally advanced settings, as demonstrated by ADAURA, NeoADAURA, and LAURA studies, which established osimertinib as the standard of care therapy across disease stages. Despite these advances, questions remain regarding the role of chemotherapy, duration of adjuvant targeted therapy, and the integration of ctDNA-guided minimal residual disease (MRD) monitoring in the early-stage setting. For metastatic disease, frontline combination strategies, such as osimertinib plus chemotherapy (FLAURA2) and amivantamab plus lazertinib (MARIPOSA), building on the EGFR-TKI backbone have improved progression-free and overall survival, particularly in higher-risk subgroups. However, as more therapeutic options emerge in the frontline and beyond, optimal treatment selection and sequencing become increasingly complex and tailored to individual risk factors, patient preferences, and disease biology. Following progression on third-generation TKIs, potential avenues for overcoming resistance include mechanism-based strategies targeting MET amplification or EGFR C797S, as well as mechanism-agnostic approaches such as bispecific antibodies and antibody-drug conjugates (ADCs). Collectively, these recent advances reflect the dynamic nature of the therapeutic landscape for EGFR-mutant NSCLC, which is becoming increasingly individualized, mechanism-informed, and resistance-adaptive, in efforts to achieve durable systemic and intracranial disease control.